Enzymatic pretreatment of lignocellulosic biomass: An overview - Mustafa, A. H.; Rashid, S. S.; Ab Rahim, Mohd Hasbi; Rasidi, R.; Musa, W. A. M.; Sikder, Md. Belal Hossain; Sasi, A. A. (Universiti Malaysia Pahang, 2022)
Lignocellulosic biomass is nature's most abundant alternative source of biofuels replacing traditional fossil fuels. Globally, more than 70% of renewable energy depends on biomass and contributes 14% of the total energy supply. The pretreatment of lignocellulosic biomass is to remove lignin, modify the lignin structure, reduce the cellulose crystallinity and increase the porosity and surface area of lignocellulosic material. The pretreatment of lignocellulosic biomass is one of the most expensive steps for biomass conversion and consumes about 40% of total costs. Traditionally physical and chemical methods have been used for the pretreatment of lignocellulosic biomass. However, these methods are unsustainable and have a huge negative impact on the environment. Pretreatment by the lignocellulosic laccase enzyme can overcome these problems. So the pretreatment of lignocellulosic biomass has been studied, presenting special attention to the enzymatic pretreatment of lignocellulosic biomass.